MLVA and LPS Characteristics of Brucella canis Isolated from Humans and Dogs in Zhejiang, China - Piao, Dongri; Wang, Heng; Di, Dongdong; Tian, Guozhong; Luo, Jiantong; Gao, Wenjie; Zhao, Hongyan; Xu, Weimin; Fan, Weixing; Jiang, Hai (Frontiers in Veterinary Science, 2017)
Background Brucella canis is a pathogenic bacterium that causes brucellosis in dogs, and its zoonotic potential has been increasing in recent years. B. canis is a rare cause of human brucellosis in China, where B. melitensis has been the predominant species associated with human and animal brucellosis outbreaks. In late 2011, a case of a B. canis infection was detected in a human patient in Zhejiang Province, China. To compare the epidemiological relationship between strains of B. canis isolated from the human patient and the canine strains isolated from Hangzhou, capital of Zhejiang Province, and from other China regions, a multiple-locus variable-number tandem-repeat analysis (MLVA-16), which was divided into panel 1 and panel 2 (including panel 2A and panel 2B), was performed. In addition, twenty-one genes, involved in the lipopolysaccharide-synthesis, were sequenced and compared with the B. canis RM6/66 strain. Results A total of 32 B. canis strains isolated from throughout China were divided into 26 MLVA types using MLVA-16 (HGDI of 0.976). The HGDI indices for various loci ranged between 0.000-0.865. All four Hangzhou isolates were indistinguishable using panel markers (genotype 3) and panel 2A markers (genotype 28). However, these strains were distinctly different from other isolates from Beijing, Jiangsu, Liaoning, and Inner Mongolia at bruce09. The emergence of a human B. canis infection was confined to a community-acquired sporadic case, which might raise new awareness and interest for such infection in humans. Comparative analysis indicated B. canis from canines and humans have few differences in lipopolysaccharide-synthesis locus. Conclusion The comprehensive approaches have been used to analyze human and canine B. canis isolates, including molecular epidemiological and genetic characteristics. Further detailed analysis of the whole genomic sequencing and transposon mutagenesis will contribute to understanding of the pathogenicity of B. canis in humans